Soils and erosion surfaces: a contextualization of landscape evolution in the Southern Espinhaço Range (SdEM), Minas Gerais (Revista Espinhaço, 2020)
The study investigated the landscape evolution of Serra do Espinhaço Meridional (SdEM), MG, through the macromorphological, mineralogical, micromorphological and chemical characterization of soils developed from the main regional lithostratigraphic units. There are mainly Neossols and Cambisols, decapitated by erosion and covered discordantly by a paleopavement. Considering climatic variations, erosion surfaces and recent soil dating, we understand that after long desert conditions in the Cretaceous (Post-Gondwana Surface) until the Paleocene (South American Surface), there was an abrupt climatic variation in the Eocene, in which hot and humid conditions formed the weathered mantles and the dismantling of the quartz veins from the underlying geological units (Supergroup Espinhaço). These conditions were also present during the Miocene, disappearing in the Pliocene, where the installation of a new desert climate promoted the disappearance of vegetation and the consequent erosiondecapitating of soil profiles. In this context, the aforementioned regional paleo-pavement was formed and interpreted as contemporary to the Surface Velhas. Over it, during the Quaternary, countless peatlands were formed, suggesting mild regionalclimatic conditions.
Keywords: Paleo-pavement; duricrusts; decapitated soils; erosion surfaces; climatic variations